Chemerin affects blood lipid profile of high-fat diet male mice in sedentary and exercise states via glucose and lipid metabolism enzymes - Jia, Yi; Yang, Yanan; Qu, Jing; Yin, Lijun; Wang, Xiaohui (Endocrine Connections, 2024)
Adipokine chemerin plays important roles in disorders of glucose and lipid metabolism of obesity and obesity-related diseases, and exercise-induced improvement of glucose and lipid metabolism is closely related to the decrease of chemerin, but the mechanisms by which chemerin regulates glucose and lipid metabolism remain unclarified. Hypotestosterone induces male obesity and disorders of glucose and lipid metabolism through androgen receptor (AR) and its target genes: glucose and lipid metabolism-related molecules (including FOXO1, PEPCK, PGC-1α, and SCD1). Recently, the link between them has been reported that chemerin modulated the secretion of androgen. In this study, global chemerin knockout (chemerin (−/−)) mice were established to demonstrate the roles of chemerin in regulating blood glucose and blood lipid of mice under diet (high-fat (HFD) and normal diet) and exercise interventions and then to explore its mechanisms (AR – glucose and lipid metabolism enzymes). We found that the blood lipid and adipocyte size were low accompanied by the improvements in the levels of serum testosterone, gastrocnemius AR, and gastrocnemius FOXO1, SCD1, and PGC-1α in HFD chemerin (−/−) mice, but exercise-induced improvements of these indicators in HFD WT mice were attenuated or abolished in HFD chemerin (−/−) mice. In conclusion, the decrease of chemerin improved the blood lipid profile of HFD male mice at sedentary and exercise states, mediated partly by the increases of testosterone and AR to regulate glucose and lipid metabolism enzymes. To our knowledge, it is the first report that chemerin’s regulation of glucose and lipid metabolism might be mediated by testosterone and AR in vivo .